Person means relation - Walsh, David 1950-; Walz, Matthew D. (St. Augustine's Press, 2024)
"David Walsh offers a moving reflection on personhood, beginning from the connection between person and relation established in the Trinitarian theology of St. Thomas Aquinas. Although Thomas did not apply this insight to persons more generally, Walsh argues, there is enough to suggest the path he might have taken. The paradox of a figure like Thomas is thathis own intense interior life largely eludes the philosophical means at his disposal. To know persons, we can now see, is to know what is going on within them. This understanding is largely the fruit of a later philosophical revolution, a fruit toward which Thomas may have pointed, and which he might well have welcomed. As such it remains the task we have inherited and the one in which the modern world distills what is best within it. The University of Dallas Aquinas Lecture for 2023, Person Means Relation is published here with a response by Matthew Walz and a reply by David Walsh."--Back cover
Keywords: Thomas -- von Aquin, Heiliger -- 1225-1274; Trinitätslehre; Beziehung; Person; Thomas / Aquinas, Saint / 1225?-1274 / Criticism and interpretation; Persons; Personnes; people (agents); lectures; Lectures; Essays; Conférences